Metodologia da resolução de problemas no planejamento de atividades para a transição da Aritmética para a Álgebra - Pimentel, Danilo Eudes (2010)
Difficulties in learning algebra found on high school, especially among students of the first year have motivated this research, in order to discover and understand the origins of the problem and consider proposals for possible solutions. The first target of the present research was to explore the possible causes of difficulties on the transition from arithmetic to algebra, which should be done in the second half of elementary school but occurs most notably in the eighth year / seventh grade. Activities configured as problem solving were planned and implemented to detect problems and to support the introduction to algebraic reasoning on three groups of seventh grade students at Escola Estadual Professor Euclides de Carvalho Campos , Botucatu, SP. The objectives of those activities are: 1 Search the steps involved in planning activities for teaching algebra; find the students difficulties in its learning; 2 Implement classroom activities in the seventh grade; collect and analyze the results in order to support the dissertation work and prepare proposals to assist the learning of algebra. In order to reach it, the problem solving methodology was used with proposals for contextual problems involving modeling problems with first-degree equations, linear systems, geometry and counting. In addition to explanative lessons, in which the results were synthesized, the group work and participatory learning were emphasized. As a result, the students shown their difficulties to discern the role of the unknowns in the equation s solving, the meaning of characters as variables in modeling problems and also a strong tendency of trying to solve only arithmetic s exercises, especially through the method of trial and error. The present research examined the difficulties found as by the points of view of the theoretical conceptual transition from arithmetic to algebra as by the contextual problem solving methodology, which involves the school planning and the social environment.